2006
DOI: 10.1507/endocrj.k06-026
|View full text |Cite
|
Sign up to set email alerts
|

Hypoadiponectinemia in Lean Lactating Women: Prolactin Inhibits Adiponectin Secretion from Human Adipocytes

Abstract: Abstract. Adiponectin is an adipocyte-derived hormone involved in glucose, lipid and energy metabolism. A low plasma adiponectin concentration is associated with insulin resistance, obesity and atherosclerosis. In women, energy homeostasis is remarkably changed during gestation and lactation in order to supply sufficient nutrition for a fetus or newborn. In this study we aimed to elucidate the physiological impact of gestation and lactation on the plasma adiponectin levels and the influence of reproduction-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
46
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 34 publications
4
46
0
1
Order By: Relevance
“…Whereas serum adiponectin levels are unchanged in PRLR- [6] or PRL-knockout mice [25], PRL at very high doses inhibits adiponectin production in cultured human adipose tissue and in mice in vivo [6,31]. Lower circulating adiponectin levels were reported in lactating women, with inhibition of adiponectin production in cultured human adipocytes by PRL [32]. These discrepancies are likely due to differences in experimental design, doses of PRL, gender or species.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas serum adiponectin levels are unchanged in PRLR- [6] or PRL-knockout mice [25], PRL at very high doses inhibits adiponectin production in cultured human adipose tissue and in mice in vivo [6,31]. Lower circulating adiponectin levels were reported in lactating women, with inhibition of adiponectin production in cultured human adipocytes by PRL [32]. These discrepancies are likely due to differences in experimental design, doses of PRL, gender or species.…”
Section: Discussionmentioning
confidence: 99%
“…39 On the other hand, other investigators found hypoadiponectinemia during the 3 rd and 4 th day postpartum in normal lactating women. 40,18 It has been suggested that this hypoadiponectinemia might be due to the suppression of adipocyte-produced adiponectin by prolactin. 40,41 Otherwise, the significant decrease of the studied cytokines during the early postpartum period in pregnancies with GDM in this study could be explained by the withdrawal of cytokines produced by the placenta during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…40,18 It has been suggested that this hypoadiponectinemia might be due to the suppression of adipocyte-produced adiponectin by prolactin. 40,41 Otherwise, the significant decrease of the studied cytokines during the early postpartum period in pregnancies with GDM in this study could be explained by the withdrawal of cytokines produced by the placenta during pregnancy. 8,9,27 The role of the placenta in the production of adiponectin and IL-1β during pregnancy is further reinforced by the non-significant but clear downward trend of these cytokines during third day postpartum found in pregnancies without GDM.…”
Section: Discussionmentioning
confidence: 99%
“…One study conducted in lean pregnant women demonstrated that PRL could cause insulin resistance in adipocytes by suppressing adiponectin production and secretion (38). This mechanism is plau- sible, because low levels of adiponectin can be associated with obesity and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%